PHENOMENOGRAPHY ANALYSIS OF STUDENTS’ HISTORICAL THINKING ABILITY IN STUDYING SOCIAL HISTORY - Agus Mulyana; Yeni Kurniawati (LPMPP Universitas Negeri Yogyakarta, 2020)
The Marton Phenomenography Analysis model is interesting to apply because it has a significant characteristic of learning that is based on two academic learning patterns, namely